Influence of different separating mediums applied on the immediate dentin sealing in the tensile strength of temporary restorations - Simões, Ingrid Ísis Nogueira; Reis, Kátia Rodrigues (Brazilian Dental Science, 2022)
Objective: To evaluate the ability of different separating mediums to prevent adhesion between provisional restorations and hybridized dentin surfaces when used with the Immediate Dentin Sealing technique (IDS). Material and Methods: 120 extracted human teeth — 40 premolars and 80 molars — were selected to integrate acrylics samples separated into 4 different groups (n=10) according to the separating medium used for IDS protection. Forty samples were made of three teeth mounted in a self-cure acrylic resin block (Jet, Classic, São Paulo, Brazil) arranged side by side, simulating the positioning and proximal contacts present in the dental arch between the second premolar, first molar and second molar. A standard dental preparation for ultra-thin occlusal veneer was performed and complete occlusal dentin exposure was achieved by selective removal of the occlusal enamel with a high-speed conical round burr (Code: 1801.4138 FG, KG Sorensen, Medical Burs Ind. e Com. de Pontas e Brocas Cirúrgicas Ltda, São Paulo, Brazil). Dentin hybridization were performed on the control group and 3 different groups of separating mediums (n=10): PC—commercial provisional separating agent (Pro-V Coat, Bisco, Schaumburg, USA); GG—glycerin gel (K-Y Gel; Johnson & Johnson Industry and Commerce LTDA, São Paulo, Brazil); PJ—petroleum jelly (Rioquímica, São Paulo, Brazil). Provisionalization were manufactured on the prepared teeth. After 2 weeks, the tensile test was performed, and the analysis of the failure pattern was performed by 3D laser confocal microscopy and Scanning Electron Microscopy (SEM). The data were analyzed with the 1-way ANOVA and the Tukey test (a = 0.05). Results: Significantly lower tensile strength values were found for the commercial provisional separating agent (30.39 ± 10.01 N) compared to others (p < 0.05). Conclusion: The commercial provisional separating agent showed greater effectiveness on protecting hybridized dentin against the provisional restorations. KEYWORDS Dental bonding agent; Dental restoration temporary; Immediate dentin sealing.